Labor market matching with application to Finnish data - Vento, Ville (2014)
This thesis studies labor market matching and takes use of a matching function, which describes the technology how unemployed job seekers and vacant jobs search, meet and form new employment relationships. The goal of the study is twofold: First is to provide a comprehensive critical review of previous literature covering both micro models as well as empirical applications. Major limitations in empirical studies are imperfect measures of variables as well as inability to account for all relevant factors making results methodology-sensitive. The second contribution is to estimate a matching function for Finland using annual data from 2006-2012 and thus giving the most recent knowledge on the matching process in the regional labor markets in Finland. The study uses both conventional panel data concepts and stochastic frontier analysis allowing differentiation of matching technology from inefficiency. The results are mainly in line with previous studies and indicate that one percent increase in the number of unemployed job seekers increases the outflow into employment by 0,9 percent whereas same increase in the number of vacancies reported at local labor offices only raises the outflow by 0-0,1 percent. The data shows that most vacancies are filled during a year, but they do not seem to help much the local unemployed, as many of those vacancies are filled by non-unemployed job seekers as well as job seekers from other regions. Efficiency in matching has decreased during the research period and it is negatively correlated with the share of long-term unemployment and positively correlated with the shares of unemployed job seekers younger than 25 and older than 55 years old and the share of unemployed in active labor market policies.